Workload of physiotherapy procedures in the adult intensive care unit: a descriptive study in a Brazilian teaching hospital - Colombo, Alexandra Siqueira; da Silveira, Leda Tomiko Yamada; Fu, Carolina (Physiotherapy theory and practice, 2025)
Physiotherapy techniques applied in intensive care units (ICU) aim to counteract functional decline and manage acute respiratory conditions. Treatment strategies vary depending on factors such as diagnosis, disease severity, and costs. Staffing resources and workload impact the duration and frequency of interventions. Understanding the workload of procedures may enhance patient care quality. To determine the frequency, duration, and workload of physiotherapy procedures applied to adult ICU patients. Secondarily, we analyzed the time spent per shift on teaching-related and non-procedure-related activities. Longitudinal panel study conducted in a 12-bed university hospital. Physiotherapy sessions applied to adult ICU patients were included. The list of procedures was derived using the Delphi method. The investigator followed physiotherapists to measure the duration of procedures and calculate a workload index for each (determined as duration x frequency). Duration of teaching-related and non-procedure-related tasks was also recorded. A total of 339 physiotherapy sessions were analyzed across 79 shifts, involving 181 patients and 19 physiotherapists. Procedures with the highest workload index were: out-of-bed mobilization, patient positioning, passive limb mobilization, active exercises, artificial airway suctioning, and equipment management. Time distribution across the shifts was as follows: direct patient care 40% (SD 12%), non-procedure-related activities 20% (SD 6%), and teaching-related activities 10% (range: 4%-19%). The procedures with the highest workload index were those directly related to rehabilitation, such as mobilization and exercises, and those not specific to patient condition, like positioning and equipment management. Physiotherapists spent most of their time in direct patient care, followed by indirect care activities and teaching.